Auditoría financiera para determinar la razonabilidad de la información financiera, empresa Multicomercio Quintana Disensa, cantón Chimbo, período 2018 - Mariana Alexandra, Verdezoto Morejón (2021)
ABSTRAC This investigative work called “FINANCIAL AUDIT TO DETERMINE THE REASONABILITY OF THE FINANCIAL INFORMATION OF THE MULTICOMERCIO QUINTANA DISENSA COMPANY, CHIMBO CANTON, PERIOD 2018”, aims to perform a financial audit in order to determine the reasonability of the financial information of the Multicomercio Quintana Disensa company of the Chimbo canton, period 2018. In the methodology of this research, the deductive and analytical method were used, which were fundamental for the development of the Audit, to carry out a more detailed study, we worked with two types of population, documental and human resources, from which the respective samples were taken in order to carry out a more exhaustive study. Finally, the financial audit phases were developed, in the planning stage, a prior visit to the company was made in order to obtain the necessary information for the audit development, in the development phase, each of the selected components was analyzed and the findings were determined and in the last phase, which is the communication of results, a final audit report was made, in which a qualified opinion was given on the reasonability of the financial information of the Multicomercio Quintana Disensa company. Keywords: audit, financial information, reasonability, internal control Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301